Police failure in identifying victims of human trafficking for sexual exploitation: an empirical study in Vietnam - Nguyen, Oanh (Journal of crime and justice, 2020)
Police officers are considered as key actors in responding to the illicit trade in people in Vietnam. Based on 150 surveys and 25 in-depth interviews with these officers in five provinces/cities and one ministerial agency, this study explores challenges in identifying victims of sex trafficking. This research determined some police-related obstacles to identification, including lack of priority for identification of victims, stigmatization of sex workers, ignorance of ethnic minorities’ immigration for work, low quality of training courses, weaknesses in foreign and ethnic minorities’ languages, and ineffectiveness of interagency cooperation. The purpose of underlining such problems is to confirm that police weakness may contribute to lowered number of identified victims of sex trafficking.